Microscopy of crustacean cuticle: formation of a flexible extracellular matrix in moulting sea slaters Ligia pallasii. (4th December 2018) - Štrus, J.; Tušek-Žnidarič, M.; Repnik, U.; Blejec, A.; Summers, A.
Abstract: Structural and functional properties of exoskeleton in moulting sea slaters Ligia pallasii from the Eastern Pacific coast were investigated with CT scanning and electron microscopy. Ultrastructure of preecdysial and postecdysial cuticular layers was described in premoult, intramoult and postmoult animals. Cuticle is a flexible extracellular matrix connected to the epidermal cells through pore channels. During premoult epicuticle and exocuticle are formed and during intramoult and postmoult endocuticular lamellae are deposited and the cuticle is progressively constructed by thickening and mineralization. Cuticle permeability, flexibility and waterproofing capacity change accordingly. Elaboration of epicuticular scales connected to an extensive network of nanotubules, establish its anti-adhesive and hydrophobic properties. Labelling with gold conjugated WGA lectins on Tokuyashu thawed cryosections exposes differences in chitin content between exocuticle and endocuticle. Histochemical staining of cuticle shows presence of acidic carbohydrates/glycoconjugates and lipoproteins in epicuticular layer. Chitin microfibrils are formed at the microvillar border of epidermal cells with abundant Golgi apparatus and secretory vesicles. Numerous spherules associated with nanotubules were observed in the ecdysial space in intramoult animals. The mineral component of the cuticle as visualized with CT scanning indicates progressive mineral resorption from the posterior to the anterior half of the body in premoult animals, its translocation from the anterior to posterior part during intramoult and its progressive deposition in the posterior and anterior exoskeleton during postmoult. Cuticle of sea slaters is a unique biocomposite and biodynamic material constantly reconstructed during frequent moults, and adapted to specific physical and biotic conditions of the high intertidal rocky zone.